Language Games and Acquisition of Speaking Skills among Students of Junior High School in Hohoe Municipality, Ghana - Oringo, Dr. James Odhiambo; Oringo, James Odhiambo (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Speaking is one of the basic language skills that students should master in order to communicate effectively and interact with others. Speaking skills are necessary for the social as well as academic life of a person by becoming responsive as well as receptive to information thus forming a favorable impression of oneself. Internationally, there is a debate that several high school graduates cannot properly speak English language and even the bright learners who get high scores in written tests cannot express themselves verbally, despite English being the official language of instruction in these schools Language learning is a hard task and it requires extraordinary efforts to realize the desirable outcomes. Language games are techniques and procedures that may be used by instructors to improve the speaking skills. Accordingly, the main objective of this study was to establish the effect of language games on acquisition of speaking skills among students of Junior High School in Hohoe Municipality in Ghana. Specifically, the study sought to establish the effect of role plays, problem-solving, puzzles, and board race games on acquisition of speaking skills among students of Junior High School in Hohoe Municipality in Ghana. The research was an empirical analysis and thus adopted an empirical research design and content analysis was used in the analysis of the qualitative data. The study revealed that language games significantly influence the acquisition of the speaking skills of the students. The study further found that using language games in teaching enhances the students’ achievement and results of speaking skills. Students enjoyed their lesson and got more motivation, interest, and confidence when learning is based on the use of language games. Hence, language games should be used as designed activities in teaching speaking skills. The study findings were generalized to students of Junior High School in Hohoe Municipality in Ghana, who like many other students in Ghana, require proficiency in speaking and writing skills, specifically in English which is used in Ghanain schools to teach subjects such as mathematics, science, social studies, art, and information and communication technology. Yet, English language is a second language to many Ghanaian students irrespective of their level in the education ladder. The outcomes of this study can be useful to Ghanian schools, researchers, scholars and the Government of Ghana.